Equitable Participant Recruitment in U.S. Clinical Research: A Narrative Review and Multilevel Framework - Olufisayo Ezekiel Ogunbayo (International Journal of Advanced Multidisciplinary Research and Studies, 2026)
Persistent underrepresentation in U.S. clinical research can limit the applicability of evidence, constrain equitable access to research opportunities, and obscure clinically important variation in intervention effects and harms. This narrative review critically synthesizes contemporary evidence on equitable participant recruitment and proposes a multilevel framework linking institutional capacity, community trust and institutional trustworthiness, and participant engagement. PubMed and authoritative U.S. policy sources were searched through July 31, 2026, using concepts related to recruitment, enrollment, representation, underserved populations, community engagement, trust, site access, eligibility, participant burden, and decentralized research. Priority was given to U.S.-focused empirical studies, recent reviews, consensus reports, and federal guidance, supplemented by reference-list and related-article searching. The evidence supports a research-system model of recruitment equity. Institutional capacity shapes where studies are located, who is eligible and referred, and whether sites can provide language, navigation, scheduling, accessibility, and financial support. Community trust is more appropriately considered alongside institutional trustworthiness, including transparency, continuity, shared decision-making, and responsiveness to community priorities. Participant engagement depends on understandable communication, voluntary decision-making, and reduction of geographic, financial, caregiving, linguistic, disability-related, and digital burdens. Strategies are most credible when implemented as coordinated packages rather than isolated outreach tactics. The proposed framework positions accessibility, relevance, trustworthiness, shared power, burden reduction, and accountability as cross-cutting mechanisms linking institutional, community, and participant domains to equity-sensitive recruitment outcomes. The framework is evidence-informed but not yet validated and should be prospectively evaluated and refined with stakeholders.